INTEGRATED APPROACH TO ASSESSING THE SEISMIC HAZARD OF URBAN AREAS IN SOUTHERN PRIANGARIE (CASE OF THE LEFT BANK OF THE ANGARA RIVER IN IRKUTSK) - A. Yu. Eskin; V. I. Dzhurik; S. P. Serebrennikov; E. V. Bryzhak (Геодинамика и тектонофизика, 2018)
Seismic hazard assessment with the use of an integrated approach is discussed on the case of the left bank of the Angara river in Irkutsk, Russia. Potential earthquake focal zones have been identified in the study area. A brief overview of fault tectonics, seismology and seismogeology of the study area is presented. The map of the epicenters of local earthquakes and the map of active faults in the study area show the magnitudes of potential seismic events in the potential earthquake focal zones. The methodology of instrumental measurements and the methods of seismic hazard assessment are considered in detail. Calculations are based on the data obtained by the instrumental methods of seismic microzoning. Theoretical seismic effects on typical ground conditions are calculated, and the estimations are obtained with reference to maximum accelerations for predicted strong earthquakes. Estimated are potential seismic effects of probable strong earthquakes on the foundations of structures in the study area. Based on the estimations, an initial signal is formed (taking into account the potential earthquake focal zones, their parameters and the spectral composition of vibrations corresponding to the local earthquakes), and a required set of seismic models is developed in order to quantify the parameters of soil motions that may take place in the event of a strong earthquake. The experimental methods provided the data on the seismic properties of the reference and investigated soils, the propagation rates of seismic waves in such soils, and the pattern of microseism levels, as required for a valid estimation of seismic effect parameters by the seismic rigidity method and the microseism technique. Currently, both methods are by far the most effective in determining the seismic hazard of the territories. Statistical analysis was carried out using the calculations and the simulation data to more clearly determine the scatter of the results obtained. The seismic hazard of the study area is assessed based on the results of this study.